An evaluation of cognitive behavioral therapy for insomnia: A systematic review and application of Tolin's Criteria for empirically supported treatments. Issue 4 (4th June 2020) - Boness, Cassandra L.; Hershenberg, Rachel; Kaye, Joanna; Mackintosh, Margaret‐Anne; Grasso, Damion J.; Noser, Amy; Raffa, Susan D.
Abstract: The American Psychological Association's Society of Clinical Psychology recently adopted the "Tolin Criteria" to evaluate empirically supported treatments. These criteria better account for the strength and quality ofrapidly accumulating evidence bases for various treatments. Here, we apply this framework to cognitive behavioral therapy for insomnia (CBT‐I). Following procedures outlined by Tolin, McKay, et al. (2015), Step 1 included an examination of quantitative systematic reviews; nine met inclusion criteria. Step 2 evaluated review quality and effect size data. We found high‐quality evidence that CBT‐I produces clinically and statistically significant effects on insomnia and other sleep‐related outcomes. Based on the Tolin Criteria, the literature merits a "strong" recommendation for CBT‐I. This report is a working model for subsequent applications of the Tolin Criteria.